The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1093/ajcp/73.1.79
|View full text |Cite
|
Sign up to set email alerts
|

A Clinically Applicable High-pressure Liquid Chromatographic Method for Measurement of Serum Theophylline, with Detailed Evaluation of Interferences

Abstract: A high-pressure liquid chromatographic method for the routine measurement of serum theophylline that is accurate, specific, and sensitive is presented. It is technically simple, requires only 50 microliter serum, and takes relatively little technician time. Values for theophylline in sera obtained by this method correlate well with those obtained by use of a gas-liquid chromatographic method (r = 0.980) and with values obtained by the commonly used spectrophotometric method (r = 0.939) when the latter is free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Serum IgE was quantified by solid-phase enzyme immunoassay (Johansson, 1978;Yman et al, 1981) using Abbott IgE-EIA kits (Abbott Laboratories, Chicago, II, USA). Plasma theophylline and cAMP measurement Plasma theophylline concentrations were assayed by high-performance liquid chromatography (Ou et al, 1982;Weidner, 1980) and plasma cAMP levels by a competitive protein binding assay (Gilman, 1970), using a cAMP liquid scintillation assay kit from Amersham (Tovey et al, 1974).…”
Section: Serum Complement and Ige Measurementmentioning
confidence: 99%
“…Serum IgE was quantified by solid-phase enzyme immunoassay (Johansson, 1978;Yman et al, 1981) using Abbott IgE-EIA kits (Abbott Laboratories, Chicago, II, USA). Plasma theophylline and cAMP measurement Plasma theophylline concentrations were assayed by high-performance liquid chromatography (Ou et al, 1982;Weidner, 1980) and plasma cAMP levels by a competitive protein binding assay (Gilman, 1970), using a cAMP liquid scintillation assay kit from Amersham (Tovey et al, 1974).…”
Section: Serum Complement and Ige Measurementmentioning
confidence: 99%
“…These drugs include some of the cephalosporins (Agdeppa and Lipton, 1980;Frutkoff et aI., 1982;Kelly et aI., 1978;Robinson et aI., 1978;Weidner et aI., 1980), ampiciIIin and methiciIIin (Lam et aI., 1979;Soldin and Hill, 1977a), sulphamethoxazole (Bowman et al, 1980;McKenzie et aI., 1978;Weidner et aI., 1980), sulphafurazole (sulfisoxazole) [Lam et aI., 1979;Weidner et al, 1980], the trisulphapyrimidines (Bond and Thornton, 1979), and chloramphenicol (Weidner et aI., 1980). Other methods should be selected when these drugs are co-administered with theophylline, otherwise the procedure should be modified to include an extraction step or the change of the internal standard (when the peak of the interfering drug appears very close to the position of the internal standard).…”
Section: Antibioticsmentioning
confidence: 99%
“…Modifications, which include a change of the column or of the mobile phase, could eliminate some of the interferences as well (Bowman et aI., 1980;Miksic and Hodes, 1979). 79 Weidner et al (1980) suggested a second reading of a sample with interference at a lower flow rate. This offered complete resolution of some of the peaks which overlapped with either theophylline (a positive interference) or the internal standard (a negative interference).…”
Section: Antibioticsmentioning
confidence: 99%